Advanced Chemistry - Matthews, P Philip Matthews; Philip, M. Mathews Philip (New York: Cambridge University, 1996)
Cambridge Low Price Editions are reprints of internationally respected books from Cambridge University Press. Advanced Chemistry covers the syllabuses of all the main examining boards offering A-level chemistry, and contains material suitable for students beginning undergraduate study. The author places the subject in context by discussing the nature and the wider implications and applications of chemistry. The material is divided into four parts: physical, industrial, inorganic and organic chemistry. Each part is divided into short self-contained units, each of which develops a set of well-defined themes or concepts. Students may work through the units in order, or individual units may be used separately.
Keywords: Chemistry